The impact of social media addiction on the negative emotions of adolescent athletes: the mediating role of physical appearance comparisons and sleep - Lin, Weilong; Cen, Zhenyu; Chen, Ying (Frontiers in Public Health, 2025)
Extensive use of social media is commonly associated with the development of social media dependency and amplification of adverse emotions among adolescent athletes. Descriptive statistics, correlation analysis, and path analysis were employed to investigate the impact of social media addiction on the negative emotions experienced by adolescent athletes. This study included a sample of 362 adolescent athletes (aged 14–21) participating in various sports events at training facilities in Guangdong and Hunan. Data collection was performed using the Social Media Addiction Scale, Body Appearance Comparison Scale, Pittsburgh Sleep Quality Index (PSQI), and the Depression, Anxiety, and Stress Scale (DASS-21). The findings suggest that social media addiction contributes directly to heightened negative emotions in adolescent athletes. In addition, physical appearance comparisons and sleep quality were identified as mediating factors that intensify the influence of social media addiction in terms of negative emotions. Consequently, it is recommended to underline the importance of mental health support for adolescent athletes, implement effective strategies for managing social media use, promote healthy body image perceptions, enhance sleep quality, and address negative emotions among adolescent athletes.